A role-playing game to stimulate thinking about vineyard management practices to limit pesticide use and impacts. (20th December 2022) - Hossard, L.; Schneider, C.; Voltz, M.
Abstract: Pesticides harm the environment and the health of applicators and rural populations. Although several levers exist to help reduce agricultural pesticide use, farmers hesitate to use them because they can require specific training, costly materials, and additional worktime while often decreasing yields. In this study, our objective was to design and develop an ad hoc role-playing game that can be used to design strategies of change for agricultural practices to reduce the unwanted impacts of pesticide use at farm and watershed scale. The main challenge was to create a game that is realistic and relevant to actors while bringing new knowledge to foster learning. We developed a participatory process to build the game and then complemented it with original contributions from research: the results of innovative field experiments and the design of simple assessment indicators corresponding to the evaluation criteria of actors. Our case study was a vineyard watershed subject to heavy pesticide use. Interview surveys with farmers and workshops with local actors (including farmers) and experts were employed to build the game, which included a spatial typology of farms, a simple calculator of potential impacts, and two types of roles. In the role of winegrower, the participants propose changes in practices for a virtual farm. In the role of public administrator, they evaluate the winegrowers' requests and the evolution of potential impacts, and then suggest further changes. The game was played with local actors and experts, separately. Game results were analyzed in terms of changes in practices, subsidy requests, and the evolution of potential impacts, both at the scale of farm types and the entire watershed.In the two game sessions, all participants modified the practices of their virtual farms. This revealed common and divergent choices between the group of experts and the group of local actors. Experts requested more plot-scale subsidies. They were also more ambitious in managing fungi and decreasing glyphosate use. At the watershed scale there were few differences between the potential impacts of the strategies as designed by the two different groups. However, the different attitudes of local actors and experts revealed different perceptions on investment, risks, and subsidies.This is the first game developed at a territorial scale to co-design and assess agricultural systems aimed at reducing unwanted impacts of pesticide use. The game is limited by the absence of economic and yield impacts, which should be a priority in the development of future versions of the game. Highlights: Limiting pesticide impacts is essential for mitigating pollution in vineyard areas. A role-playing game is used to design new pesticide-saving management in vineyards. The game was found pedagogical, and useful to stimulate thinking on practice impacts. Separate sessions (experts or local actors) highlighted different risk perceptions. Sessions helped identify conditions for further changes.